Influence of high-intensity focused ultrasound (HIFU) ablation on arteries : ex vivo studies - Zhou, Yufeng (2021)
High-intensity focused ultrasound (HIFU) has been used to ablate solid tumors and cancers. Because of the hypervascular structure of the tumor and circulating blood inside it, the interaction between the HIFU burst and vessel is a critical issue in the clinical environment. Influences on lesion production and the potential of vessel rupture were investigated in this study for the efficiency and safety of clinical ablation. An extracted porcine artery was embedded in a transparent polyacrylamide gel phantom, with bovine serum albumin (BSA) as an indicator of the thermal lesion, and degassed water was driven through the artery sample. The HIFU focus was aligned to the anterior wall, middle of the artery, and posterior wall. After HIFU ablation, the produced lesion was photographically recorded, and then its size was quantified and compared with that in the gel phantom without artery. In addition, the bubble dynamics (i.e., generation, expansion, motion, and shrinkage of bubbles and their interaction with the artery) were captured using high-speed imaging. It was found that the presence of the artery resulted in a decrease in lesion size in both the axial and lateral directions. The characteristics of the lesion are dependent on the focus alignment. Acoustic and hydrodynamic cavitation play important roles in lesion production and interaction with the artery. Both thermal and mechanical effects were found on the surface of the artery wall after HIFU ablation. However, no vessel rupture was found in this ex vivo study.